The EU directive on road infrastructure safety management - Research at the national and European levels - Macedo, A. L. (2010)
Submitted by António Macedo (almacedo@lnec.pt) on 2010-05-28T17:18:11Z No. of bitstreams: 1 Abatract_RGRA_ ALM_CARD.pdf: 6686 bytes, checksum: c6963249b3d33a02eba7d2eb19cf8df8 (MD5)